Strategi Penguatan Ukhuwwah Basyariyah untuk Memperkokoh Kerukunan Sosial di Desa Purwodadi, Kecamatan Tembarak, Kabupaten Temanggung - `Arifah, Siti; Ifadah, Luluk; Arifah, Zaidatul; Nashihin, Husna (Ahdāf: Jurnal Pendidikan Agama Islam, 2024)
This research aims to explore the application of the concept of ukhuwah basyariyah (universal brotherhood) in the lives of the people of Purwodadi Village, Tembarak Subdistrict, Temanggung Regency, the majority of whom embrace Islam with a diversity of religious organization affiliations. This research uses a qualitative approach with a phenomenological method, where data is obtained through observation, participatory, semi-structured interviews, and documentation. The data were analysed using Interpretative Phenomenological Analysis, through an analysis process including reading the data in depth, grouping the data based on relevant themes, and interpreting the data by considering the social context of the Purwodadi Village community. The results showed that despite differences in worship practices and affiliations with religious organizations such as Muhammadiyah, Nahdlatul Ulama (NU), and Majelis Tafsir Al-Qur'an (MTA), the people of Purwodadi Village were able to maintain social harmony through the application of ukhuwah basyariyah values, such as ta'āwun (helping), tasāmuḥ (tolerance), and musāwah (equality). Social and religious activities that involve all residents, such as community service, Muharam gebyar, and the celebration of Islamic holidays, become a means to strengthen solidarity between residents regardless of differences in mass organizations. The strategy to strengthen ukhuwah basyariyah in this village is carried out through various approaches, including social and religious activities, sermons, recitations, and conflict mediation. Despite challenges such as mass organization fanaticism, apathy of some residents, and low awareness of diversity, the community still managed to implement ukhuwah basyariyah effectively. This research implies that the values of ukhuwah basyariyah can be the basis for building social harmony in a multiorganizational society, with education, economic empowerment, and dialogue across mass organizations as the key to the sustainability of harmony. This research contributes to the understanding of the concept of ukhuwah basyariyah in the context of a diverse society, as well as the importance of integrating these values in social and religious life.